Incarceration of the Retroverted Uterus at Term Gestation - Matsushita, Hiroshi; Kurabayashi, Takumi; Higashino, Masahiko; Kojima, Yumi; Takakuwa, Koichi; Tanaka, Kenichi (American Journal of Perinatology, 2004)
Incarceration of the retroverted uterus is a rare complication of pregnancy and rarely persists until term. The diagnosis is extremely difficult to make and a cesarean section should be performed in such cases. A 33-year-old Japanese woman was admitted at 40 weeks gestation for evaluation of preeclampsia. Vaginal examination revealed that the uterine cervix could hardly be visualized, although the fetal head was impacted in the pelvis. These findings suggested incarceration of the retroverted uterus. Magnetic resonance imaging (MRI) was performed and clarified the exact anatomical relationship and confirmed the diagnosis. She therefore underwent a cesarean section and a male infant weighing 3552 g was delivered with Apgar scores of 9 and 10 at 1 and 5 minutes, respectively. At surgery she was found to have an adhesion between the uterus and the pouch of Douglas. MRI is a useful tool in correctly making the diagnosis of uterine incarceration and facilitates preparation for a cesarean section.
Keywords: Uterine incarceration; magnetic resonance imaging; pregnancy complication